In-situ TEM irradiation creep experiment revealing radiation induced dislocation glide in pure copper. (1st September 2021) - Khiara, Nargisse; Onimus, Fabien; Jublot-Leclerc, Stéphanie; Jourdan, Thomas; Pardoen, Thomas; Raskin, Jean-Pierre; Bréchet, Yves
Abstract: In-situ TEM straining experiments were performed on pure copper to investigate the dislocation activity under heavy ion irradiation and high applied stress levels. The unpinning of dislocations from irradiation defects followed by glide was observed under irradiation at stress levels just below the critical stress for dislocation glide without irradiation. This phenomenon, unraveled for the first time in copper, has been statistically analyzed using digital image processing. Quantitative analysis of pinning lifetimes has been performed, suggesting that a cascade related mechanism is operative to explain the radiation induced dislocation glide. This work provides new insights on the irradiation creep deformation at high stress level. Graphical abstract: Image, graphical abstract